A study on porous asphaltic concrete mix and its value in pavement construction - Pagbilao, Dominador S.
The factors affecting the porosity of a porous asphaltic concrete mix was studied and the effect of these on its Marshall Stability was evaluated. Based on the results of porosity and stability tests of several mixes, the value of a porous mix design to porous pavement construction is presented.